Gender Differences in the Association Between Alcohol Use and Sedentary Behavior Among Adults. Issue 7 (September 2018) - Agrawal, Pooja; Mercer, Andrew; Hassanali, Jamila; Carmack, Chakema; Doss, Darleesa; Murillo, Rosenda
Purpose: We examined differences in the association between alcohol use and sedentary behavior by gender among adults. Design: Cross-sectional study that employs a complex, multistage stratified probability cluster sample design. Setting: National Health and Nutrition Examination Survey (NHANES) 2007 to 2014. Participants: NHANES participants aged ≥20 years and identifying as Hispanic, white, or black (N = 18 441). Measures: Demographic characteristics, sedentary behavior, and alcohol consumption. Sedentary behavior was measured based on the number of minutes of sedentary activity per week. Alcohol consumption in the last year was measured based on responses to items assessing whether the participant consumes alcoholic beverages and the number of alcoholic beverages consumed on average. Analysis: Multinomial logistic regression analysis was used to estimate associations of alcohol use with categories of sedentary behavior by gender. Results: Compared to women who reported not consuming alcohol, women who were heavy drinkers were significantly more likely to engage in high sedentary activity (odds ratio [OR]: 1.47; 95% confidence interval [CI]: 1.16-1.87), relative to low levels of sedentary activity. Similarly, women who were binge drinkers were more likely to engage in moderate levels of sedentary activity (OR: 1.39; 95% CI: 1.05-1.85). There were no significant associations between alcohol use and sedentary activity among men. Conclusion: Findings suggest that alcohol consumption should be considered in health promotion efforts targeting sedentary behavior among women.